1985
DOI: 10.3171/jns.1985.63.1.0088
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in regional cerebral metabolite values following experimental blunt head trauma

Abstract: A Remington humane stunner was used to deliver a blow to the left side of the surgically-exposed skull in ketamine-anesthetized cats. At 15 minutes after the trauma, brain tissue was frozen in situ. In animals without visible tissue hemorrhage (Grade 0) and in those with unilateral cerebral contusions involving the cerebral cortex and white matter (Grade 2), regional cerebral metabolite concentrations were measured by enzymatic-fluorometric techniques and edema was tested with an organic gradient. No substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Indeed, we previously reported finding markedly higher lactate levels following blunt head trauma in edematous white matter located near brain contusions as compared with samples from noncontused hemispheres. 42 However, elevated tissue lactate levels are also observed 8 hours after severe fluid-percussion injury in the absence of hemorrhage 19 and after plasma infusions. 34 Also, our hematomal lactate levels are only 5 to 8 mol/g (data not shown), values that are considerably lower than those present in edematous white matter.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, we previously reported finding markedly higher lactate levels following blunt head trauma in edematous white matter located near brain contusions as compared with samples from noncontused hemispheres. 42 However, elevated tissue lactate levels are also observed 8 hours after severe fluid-percussion injury in the absence of hemorrhage 19 and after plasma infusions. 34 Also, our hematomal lactate levels are only 5 to 8 mol/g (data not shown), values that are considerably lower than those present in edematous white matter.…”
Section: Discussionmentioning
confidence: 97%
“…[40][41][42] Edema was quantitated by determining the water contents of white and gray matter samples from the brain regions listed earlier. Water content was determined by weighing and then drying the samples at 100˚C for at least 24 hours to a constant weight.…”
Section: Brain Metabolite and Water Content Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagner et al 24 showed a high increase in LAC concentration in the white matter within the territory of vasogenic oedema of contused area shortly after experimental head injury in an animal model. 24 Despite the availability of reasonable evidence on correlating cerebral LAC levels with severity of TBI, the diagnostic performance of arterial LAC and its ability to reflect CNS/CSF-LAC levels in patients with isolated head injury has been inadequately studied.…”
Section: Discussionmentioning
confidence: 99%
“…This transient phenomenon may possibly contribute to the blood-brain barrier breakdown demonstrated by extravasation of Evans blue in the present study, and be associated with the immediate elevation of intracranial pressure and the development of oedema after fluid percussion brain injury in cats previously reported [19]. It also may play a role in mechanisms causing subsequent decrease in CBE…”
Section: Cerebral Blood Flow Responses To Injurymentioning
confidence: 58%